1999
DOI: 10.1046/j.1365-2036.1999.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: drug interactions with agents used to treat acid‐related diseases

Abstract: Patients with acid-related diseases often need to take multiple medications. Treatment of Helicobacter pylori infection often includes either a histamine type 2 (H2)-receptor antagonist or a proton pump (H+,K(+)-ATPase) inhibitor (proton pump inhibitor), administered in conjunction with one or more antimicrobials. Also, treatment for acid-related diseases often requires extended therapy during which many concomitant medications may be administered for concurrent disease states. Polypharmacy may be the result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 55 publications
2
64
0
4
Order By: Relevance
“…Available results suggest no significant interaction between famotidine (administered at a total dosage of 40 mg/day) and clopidogrel [Taha et al 2009]. This is consistent with the lack of effect of famotidine on cytochrome P450 isozymes [Humphries and Merritt, 1999;Humphries, 1987].…”
Section: Limitations Associated With Use Of a Protonpump Inhibitor Fosupporting
confidence: 73%
“…Available results suggest no significant interaction between famotidine (administered at a total dosage of 40 mg/day) and clopidogrel [Taha et al 2009]. This is consistent with the lack of effect of famotidine on cytochrome P450 isozymes [Humphries and Merritt, 1999;Humphries, 1987].…”
Section: Limitations Associated With Use Of a Protonpump Inhibitor Fosupporting
confidence: 73%
“…These results are consistent with famotidine's very limited ability to alter the activity of cytochrome P450 isoenzymes (25). Pantoprazole did not interact with digoxin, nifedipine, theophylline, diazepam, warfarin, phenytoin, or oral contraceptives (26). Pantoprazole has been reported to have few clinical significant drug-drug interactions (26).…”
Section: Discussionsupporting
confidence: 73%
“…Pantoprazole did not interact with digoxin, nifedipine, theophylline, diazepam, warfarin, phenytoin, or oral contraceptives (26). Pantoprazole has been reported to have few clinical significant drug-drug interactions (26).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of their excellent safety record, the relative safety of different proton pump inhibitors has been widely publicized over the last few years, with particular emphasis on drug-drug interactions. [1][2][3][4][5][6][7][8][9] It has been suggested that pantoprazole is less likely than omeprazole or lansoprazole to interact with other drugs as a result of minor differences in its metabolic profile. 10,11 In a recent retrospective survey of patient treatment records from US veterans, it was concluded that the co-prescription of omeprazole or lansoprazole with warfarin, clarithromycin or diclofenac led to an increase in adverse events, requirements for care and total costs of care.…”
Section: Introductionmentioning
confidence: 99%